Mary Douglas understanding social thought and conflict - 6, Perri 1960- (Berghahn Books, 2017)
Mary Douglas's innovative explanations for styles of human thought and for the dynamics of institutional change have furnished a distinctive and powerful theory of how conflicts are managed, yet her work remains astonishingly poorly appreciated in social science disciplines. This volume introduces Douglas's theories, and outlines the ways in which her work is of continuing importance for the future of the social sciences. Mary Douglas: Understanding Human Thought and Conflict shows how Douglas laid out the agenda for revitalizing social science by reworking Durkheim's legacy for today, and reviews the growing body of research across the social sciences which has used, tested or developed her approach